(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Modern technologies of communication systems and digital systems are considered an essential part in the life of nations and individuals in the modern world, but at the same time these systems constitute a serious threat on the security of the states. This study aimed at discussing the topic of cyberspace as a new type of conflicts and disputes between states and it shows the importance and seriousness of cyber- attacks. The study focuses on the inclusion of Cyber- attacks and Aggression against states, international actors must adopt these attacks effectively and they must find legal justification in the Public International Law Allows to use the right of self- defense in the event of an international electronic attack. However, there is no legal justification until now that allows self- defense in this type of attacks or legal item that puts these attacks under unarmed and indirect aggression.